Perlindungan Hukum Terhadap Pekerja Anak - Benjamin C Picauly (PAMALI: Pattimura Magister Law Review, 2022)
Introduction: One of the human rights that must be recognized, fulfilled and guaranteed protection by the state is human rights in the field of employment, namely the right to work and obtain work. However, the main problem in employment issues that must receive special attention is child labor.Purposes of the Research:  To analyze forms of legal protection for child labor.Methods of the Research: The research was conducted using a normative juridical method with a c statutory approach, conceptual approach and comparative approach a by specifically analyzing the performance of the institution and its authority in the implementation of law enforcement in the Maluku Sea based on the legislation which was then analyzed qualitatively.Results of the Research: Due to the lack of formal employment opportunities, many people work in the informal sector. Even so, the informal sector has not been able to provide proper welfare for workers, but it remains one of the choices of employment opportunities. This situation causes high poverty rates. As a result, many children drop out of school because they are unable to continue their education, which is quite expensive. This situation has forced many school-age children in Ambon City to work to help their families either in markets or in people's homes. Child labor is allowed as long as there is protection for child labor in accordance with applicable laws.